Wound Healing Herbal Formulation from Essential Oil of Lemongrass (Cymbopogon citratus) - Wisdawati, Wisdawati; Razak, Rais (Indonesian Journal of Pharmaceutical and Clinical Research, 2024)
Untreated wound may lead to the infection. In some countries, plants are used to cure wound traditionally. Lemongrass (Cymbopogon citratus) has various bioactive compounds, including citronellol, limonene and geraniol that perform some pharmacological activities. In this study, the essential oil of lemongrass was designed into ointment formulation since lemongrass has been reported to have a wound healing effect in mice. The wound healing ointment made from different concentration of the essential oil of Cymbopogon citratus (F1: EOCC 5%, F2: EOCC 10% and F3: EOCC 15%) using a water-removable base and the characteristic as well as the stability (texture, color, smell, homogeneity, and pH) after been stored for 14 days was also evaluated. The result showed that all formulation (F1, F2, and F3) of wound healing formulation revealed good texture, consistency, odor, color, homogeneity and compatible to the skin until 14 days of storage. However, F3 (EOCC 15%) has a strong lemongrass smell compare to the other formulations.